2018
DOI: 10.12691/ajidm-6-2-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Studies of GENXPERT versus MGIT Culture of Bronchial Lavage in Sputum Smear Negative Suspected Pulmonary Tuberculosis

Abstract: Introduction: Xpert MTB/RIF (Cepheid, USA) is an automated real-time PCR system that simultaneously detects TB and resistance to rifampicin. The test has excellent accuracy when performed on sputum and is endorsed by the World Health Organisation (WHO) and the USA Federal Drug Administration. Aims: To measure the diagnostic yield of bronchoalveolar lavage gene Xpert and compare it with traditional mycobacterial cultures in smear-negative and sputum-scarce pulmonary tuberculosis. Methods: A prospective observat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
3
1
0
Order By: Relevance
“…In the present study, out of 76 patients, 25 (32.9%) and 51 (67.1%) were females and males respectively. Similar dominance of males was shown by study done by Abhay Uppe et al, [13] in their study. There were 121 (60.5%) males and 79 (39.5%) females in study done by Abhay Uppe et al [13] Sanjay Avashia et al1 in their study revealed that 56.9% were male and 43.1% were female.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, out of 76 patients, 25 (32.9%) and 51 (67.1%) were females and males respectively. Similar dominance of males was shown by study done by Abhay Uppe et al, [13] in their study. There were 121 (60.5%) males and 79 (39.5%) females in study done by Abhay Uppe et al [13] Sanjay Avashia et al1 in their study revealed that 56.9% were male and 43.1% were female.…”
Section: Discussionsupporting
confidence: 91%
“…Similar dominance of males was shown by study done by Abhay Uppe et al, [13] in their study. There were 121 (60.5%) males and 79 (39.5%) females in study done by Abhay Uppe et al [13] Sanjay Avashia et al1 in their study revealed that 56.9% were male and 43.1% were female. Mushtaq Ahmad et al, [14] in his study found that males constituted 85.3% of patients.…”
Section: Discussionsupporting
confidence: 91%
“…The study performed in 100 patients with a high pretest probability for pulmonary Tuberculosis. Present study having 62% males comparable to Uppe et al, 6 study 9 study in which males 42.7 and females 41.6. In general TB incidence is more common in extremes of age group that is adolescents and elderly group.…”
Section: Discussionsupporting
confidence: 86%
“…The sensitivity of bronchial specimens ZN stain and CBNAAT are 48.86% and 78.89% respectively in Hazarika et al, 9 study. In Uppe et al, 6 study, the sensitivity of bronchial specimen ZN stain and CBNAAT are 76.83% and 84.15% respectively. In Khalil et al, 9 study, the sensitivity for BAL ZN stain and CBNAAT are 39.53% and 91.86% respectively.…”
Section: Discussionmentioning
confidence: 88%